1992
DOI: 10.1136/jmg.29.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Campomelic dysplasia associated with a de novo 2q;17q reciprocal translocation.

Abstract: A phenotypically female fetus with campomelic dysplasia and a de novo reciprocal translocation, 46,XY,t(2;17) (q35;q23-24), is presented. This is the second case of campomelic dysplasia in which a rearrangement involving the long arm of chromosome 17 has been identified, indicating that this is likely to be the site of the campomelic dysplasia locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 4 publications
0
24
1
1
Order By: Relevance
“…Although we excluded loss of chromosome 17 material at the insertion site, a chromosome break per se could still affect gene function as shown in campomelic dysplasia (CMPD1) with sex reversal within 17q24.3-q25.1 [Young et al, 1992;Tommerup et al, 1993;Wirth et al, 1996]. However, our patient did not display campomelia or sex reversal.…”
Section: Discussioncontrasting
confidence: 45%
“…Although we excluded loss of chromosome 17 material at the insertion site, a chromosome break per se could still affect gene function as shown in campomelic dysplasia (CMPD1) with sex reversal within 17q24.3-q25.1 [Young et al, 1992;Tommerup et al, 1993;Wirth et al, 1996]. However, our patient did not display campomelia or sex reversal.…”
Section: Discussioncontrasting
confidence: 45%
“…To date there have been 14 heterozygous mutations described in SOX9 (Foster et al, 1994;Wagner et al, 1994;Kwok et al, 1995;Cameron et al, 1996;Hageman et al, 1997) and 10 17q translocations described in 28 patients with CD (Maraia et al, 1991;Young et al, 1992;Tommerup et al, 1993;Chatters and Whitecross, 1994;Kwok et al, 1995). There have been no reported cases of patients having both a balanced 17q translocation and a mutation in SOX9 (Kwok et al, 1995).…”
Section: Mutations In Sox9 Mutations Within the Open Reading Frame Ofmentioning
confidence: 99%
“…It was speculated that disruption of 2 structural genes, Hox-2 and COLlAl, which have been mapped to 17q21-q22 and 17q21.3-922, respectively [Rabin et al, 1985;Retiefet al, 19851, may lead to variable phenotypes associated with campomelic dysplasia. Young et al [1992] reported the second case of campomelic dysplasia in which a rearrangement involving the long arm of chromosome 17 [a de nouo t(2;17) (q35;q23-24)] was present. They further called attention on loci such as growth hormoneplacental lactogen gene family [Harper et al, 19821.…”
Section: Discussionmentioning
confidence: 98%